Optimization of cognitive radio systems with energy harvesting - Pratibha (2017)
Cognitive radio (CR) enables dynamic spectrum access and offers a promising solution to the impending spectrum scarcity problem. It senses the licensed spectrum and identifies spectrum opportunities which can be utilized by the secondary users (SUs) without disrupting the primary user (PU) transmission. Hence, it improves the spectrum efficiency by opportunistic spectrum access. Power is another critical resource. Recently, a lot of work has been focused on utilizing energy-harvesting techniques to achieve self-sustaining wireless networks. Adding energy-harvesting capability will further enhance the ability of CR systems. However, the random and sporadic nature of the energy arrival poses challenges in the realization of such self-reliant CR devices. We identify and address some new interesting research problems that arise in different types of energy-harvesting CR systems. Our research is focused on finding the optimal spectrum sensing and access policies to maximize the opportunistic spectrum utilization while considering the energy uncertainty at the CR users and preventing intolerable interference to the PUs.